SISTEM KERJASAMA BURUH TANI Di Desa Saik Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi - Yunetra "; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Complex culture of art, morals, law, customs and all abilities and habits of the society.  The contiguous society can has different cultures or vice versa.  Batobo is a culture that exists in Saik Village, Kuantan Mudik District.  Batobo, which used to help between two of families, then developed into a paid cooperation system with two systems, namely rice fields and rubber fields.  The purpose of this research were to find out the Social Capital in the Farmer Labor Cooperation System and to find out the Differences in the Cooperation System on Rice Fields and Rubber Fields by using the Qualitative Descriptive Method. There were 6 informants in this research. The data data collection techniques was using interview, observation, in-depth documentation.  The results of the research showed that cooperation in the tobo group system increased social capital for groups and there were differences in social capital elements such as networks, norms and trust between rice fields and rubber fields.  Network existsted between landowners and other groups, Norms were intertwined in groups and groups with owners.  Then there was a trust between the group and the land owner in paying wages.  This collaboration system was analyzed by AGIL theory because Agil's institution is related to the characteristics of social capital, which is the network that forms the group cooperation system, then norms that are related to Integration because strong cooperation is caused by close relationships and causes the availability of establishing cooperation.  Latency is a religious institution in which trust has been instilled in a person from childhood and later is useful for maintaining a relationship in a group.  Adaptation contains economic institutions because the system of cooperation between paddy fields and rubber fields generates wages.  Then the Goal Attention that unites the whole of the related institutions.